2016
DOI: 10.17795/jjcdc-37555
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Care Model and the Self-Management in Post-Myocardial Infarction Patients: A Randomized Controlled Trial

Abstract: Background: Self-management after myocardial infarction is fundamental to effective medical treatment. Objectives: The current study aimed to investigate the effects of applying the continuous care model on self-management of a sample of Iranian patients with post-myocardial infarction. Methods: Sixty hospitalized patients were randomly allocated into control (n = 30) and intervention (n = 30) groups. Before the intervention and at the end of it, self-management of both groups was evaluated by chronic disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Our results showed the CCM increased the physical activity adherence of patients with MI. In line with the current study, the implementation of a follow-up care model increased the physical activity adherence in patients with MI (Akbari et al., 2015, 2017), heart failure (Sadeghi et al., 2009) and type 2 diabetes (Shahsavari and Foroghi, 2015). A study by Redfern et al.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results showed the CCM increased the physical activity adherence of patients with MI. In line with the current study, the implementation of a follow-up care model increased the physical activity adherence in patients with MI (Akbari et al., 2015, 2017), heart failure (Sadeghi et al., 2009) and type 2 diabetes (Shahsavari and Foroghi, 2015). A study by Redfern et al.…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed the CCM increased the physical activity adherence of patients with MI. In line with the current study, the implementation of a follow-up care model increased the physical activity adherence in patients with MI (Akbari et al, 2015(Akbari et al, , 2017, heart failure (Sadeghi et al, 2009) and type 2 diabetes (Shahsavari and Foroghi, 2015). A study by Redfern et al on the survivors of acute coronary syndrome showed that a face-to-face counselling session for 1 h and four phone calls of 10 min in three months improved physical activity for more than a year (Redfern et al, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have suggested that theory-based nursing interventions in CHD management had success in decreasing blood lipid concentrations, blood pressure, and re-hospitalization rate, and may enhance medication adherence, better adaptation to diet modifications and physical activity recommendations, and thus improved QoL (Faroughi et al, 2021;Mohammadpour et al, 2015;Turan Kavradim & Canli Ozer, 2020;Yildiz & Kasikci, 2020). (Akbari et al, 2017;Akhlaghi et al, 2021;Javadzade et al, 2018). However, to the best of our knowledge, no systematic review or meta-analysis has examined the effects of theory-based nursing interventions in CHD management, and no firm conclusion on this issue has been made so far.…”
Section: Introductionmentioning
confidence: 99%
“…Theory‐based nursing interventions play a vital role in changing unhealthy behaviors (Smith & Parker, 2015). Considering previous clinical studies in CHD management, while some studies were not conducted based on a specific nursing theory, some of those directly implemented nursing theories like Pender's health promotion model (HBM), transtheoretical model (TTM), Orem's self‐care deficit theory, Roy's adaptation model (RAM), and continuous care model (CCM; Akbari et al,2017 ; Faroughi et al, 2021; Turan Kavradim & Canli Ozer, 2020; Yildiz & Kasikci, 2020; Zhu et al, 2014). The HBM includes several concepts like perceived susceptibility, seriousness, benefits, and barriers to adopting a behavior, tips to take an action, and self‐efficacy that anticipates why people will act to control diseases and related problems (Champion & Skinner, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation